Improving the Quality of Mother-Adolescent Relationship Through Communication Skills Training - Martiani Martiani; Sri Lestari; Wisnu Sri Hertinjung (JIP (Jurnal Intervensi Psikologi), 2021)
The less quality of mother-adolescent relationship is indicated by the unwillingness of adolescent to talk about their problem to mother and the emergent of mother-adolescent conflict. This research aim to prove the effectiveness of communication skills training to increase the quality of mother-adolescent relationship. This research tests the hypothesis that communication training can improve the quality of mother and teen relationship. The quality of mother-adolescent relationship was measured using the scale of mother-child relationship. The participants were 18 mothers with Senior High School of education and that have adolescent children. The experimental design used was a pre-test post-test control group design. The result shows that communication skills training can effectively increase the quality of mother-adolescent relationship. After a mother participates in training, teenagers feel comfortable telling their problems to mothers and feel understood.